The construction of the school curriculum: reflections about cultural difference - Tura, Maria de Lourdes Rangel; Pereira, Talita Vidal (Education Policy Analysis Archives, 2014)
In this article we question patterns of curricular production which are based on the idea that structured knowledge must occupy a central position, when a curriculum supports multiple concepts of teaching. Using post-structuralist and post-functional research, highlighting Ernesto Laclau, and the post-colonials, especially Homi Bhabha, we defend that said logic contributes to keeping cultural differences outside of schools, overruled by a homogeneous culture considered more adequate to form citizens. In our view, this perspective is still common in discourses about education, and is responsible for policies that have deepened outside control over schools, especially through students’ performances and results measuring mechanisms. Therefore, they play a part in reducing education to nothing beyond teaching, and in silencing cultural differences. We assume here that schools are in-between places where multiple cultures meet, and it is our statement that these cultures must be incorporated into school processes.